2010
DOI: 10.1016/j.isprsjprs.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A pre-screened and normalized multiple endmember spectral mixture analysis for mapping impervious surface area in Lake Kasumigaura Basin, Japan

Abstract: a b s t r a c tThe impervious surface area (ISA) has emerged not only as an indicator of the degree of urbanization, but also as a major indicator of environmental quality for drainage basin management. However, since almost all of the methods for estimating ISA have been developed for urban environments, it is questionable whether these methods can be successfully applied to drainage basins, such as those found in Japan, which usually have more complicated vegetation components (e.g. paddy field, plowed field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
0
39
0
2
Order By: Relevance
“…For the second example, researchers using Landsat 5 TM images from 1987, 1999, 2000, and 2007 analyzed impervious surface changes as an environmental health indicator for Lake Kasumigaura Basin, Japan (Lake Kasumigaura is the second largest lake in Japan) [52]. Their results showed that, by 1987, the watershed had already been impacted by land use change (all sub-basins had at least 10 % impervious surfaces).…”
Section: Urban Land Use and Hydrologymentioning
confidence: 99%
“…For the second example, researchers using Landsat 5 TM images from 1987, 1999, 2000, and 2007 analyzed impervious surface changes as an environmental health indicator for Lake Kasumigaura Basin, Japan (Lake Kasumigaura is the second largest lake in Japan) [52]. Their results showed that, by 1987, the watershed had already been impacted by land use change (all sub-basins had at least 10 % impervious surfaces).…”
Section: Urban Land Use and Hydrologymentioning
confidence: 99%
“…Yang used the LSMA method with multiple endmembers to obtain impervious surface information from the area of Lake Kasumigaura in Japan. The total root-mean-square error was reduced by 5.2%, but some high and low impervious surface areas were still undervalued or overestimated [23]. Lu used the LSMA model to obtain the impervious surfaces in a rural-urban fringe district, and the results showed that the impervious surface values in the rural-urban fringe district were overestimated by 50-60% [24].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (2010) ressaltam a importância dessa técnica para análise espacial de bacias de drenagem, afirmando que as técnicas de sensoriamento remoto possuem a inerente habilidade de prover informação temporal e espacial sobre a superfície terrestre e podem ser a única forma para monitorar em larga escala as mudanças no uso da cobertura terrestre ao longo de uma bacia de drenagem.…”
Section: Introductionunclassified